PENGARUH MOTIVASI DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS DI SMPN 13 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack:This study aims to determine how the condition of student motivation, discipline of student learning and student achievement at SMP 13 Pekanbaru and to know how to influence the motivation and discipline of student learning on student achievement in social studies at SMP 13 Pekanbaru. The population in this study were students of class VIII SMPN 13 Pekanbaru as many as 380 students. The sampling technique in this study using a nonprobability sampling, sample in this study is 79 samples. Data were collected using questionnaires and documentation. Data were analyzed using multiple linear regression analysis, t test and F test with significance level of 0.05%.. Based on the results of the study showed that motivation and discipline to learn simultaneously positive and significant impact on student achievement. It is based on the results of the analysis which shows the calculation results of Ftest (11.112)> F table (3.12) with Sig. (0,000) <0.05. Furthermore, by t test turns each independent variable affects the dependent variable is the motivation to learn an effect on student achievement as evidenced where t test (4306)> t table (1.991),Furthermore, for the discipline of study showed effect on student learning achievement, This is evidenced Where that t test (3704)> t table (1.991). The predictive ability of these two variables on student achievement in the study of 22.6%. While the remaining 77.4% is influenced by other factors which are not included in this study. Keyword : motivation to learn, learning discipline, student achievement